Dyschromatosis Universalis Hereditaria - Bista, M.; Agrawal, S.; Agrawal, Y. (Kathmandu University Medical Journal, 2021)
Dyschromatosis universalis hereditaria (DUH) is a rare pigmentary genodermatosis usually inherited in autosomal dominant fashion characterized by multiple pinpoint to pea-sized hypo- and hyper-pigmented macules arranged in reticulate pattern that develops within the first few years of life. An 11 years old boy presented with multiple gradually progressive asymptomatic hypopigmented macules on hyperpigmented background on trunk, extremities and face since 2 years of age. Family history was absent. Punch biopsies revealed increased number of melanocytes in the epidermis with basal cell vacuolar alteration and pigmentary incontinence and perivascular infiltration by lymphocytes and melanophages in the dermis. We herein present a sporadic case of dyschromatosis universalis hereditaria.